Thermal evaluation of multilayer wall with a hat-stringer in aircraft design - Brazhenko, Volodymyr (Strojniški vestnik, 2022)
In the present paper, we investigate the heat transfer through the multilayer wall of aircraft cabins, as this process influences the comfortable conditions created for most passengers and crew members. The numerical modelling results and calculation of a multilayer wall with a hat-stringer in aircraft design are presented. The thermal characteristics evaluation and their relationship with the design parameters were made. The effect of the air layer size on the overall thermal resistance of the multilayer wall, taking into account the geometrical dimensions and properties of the surfaces, was studied. The relative temperature field in the insulation layer, which crosses the hat-stringer elements of the fuselage frame, is calculated. It is shown that the insufficient thickness of the layer of thermal insulation material in the zone of the hat-stringer at low temperatures leads to a significant deterioration in the multilayer wall characteristics, which can worsen the microclimatic conditions inside the aircraft cabin.
Keywords: aircraft design; hat-stringers; heat transfer; letalske kabine; matematično modeliranje; multilayer walls; numerical modelling; prenos toplote; toplotne lastnosti; toplotnoizolacijski sloji; večslojne stene